Perceived Health Status of Older People: Evidence from Sunkoshi Rural Municipality, Sindhuli, Nepal - Thapa, Naba Raj; Shrestha, Sunder (Humanities and Social Sciences Journal, 2024)
The increasing older people in a population poses significant challenges to society concerning health status, and health care. This study aims to assess the self-reported health status of older people living in rural setting. This study used primary data collected through community-based survey conducted in Sunkoshi Rural Municipality, Sindhuli. The study sample consisted of 413 older people aged 60 and above. Self-reported health status was selected as the outcome variable, while demographic and socio-economic factors were considered as independent variables. Descriptive and inferential statistics were used in data analysis. Chi-square test was performed to determine statistically significant association between outcome and independent variables. The results showed that about 63 percent of older people reported good self-reported health status, and about one in ten older people reported poor health status. The prevalence of poor health status was four times higher among the older people aged 80 and above and two times higher among the older people aged 70-79 than older people aged 60-69. Males have higher prevalence of poor health status (10%). The prevalence of good health is higher among older people who were currently married, who had primary education, and were currently working, with statistically significant differences in the self-reported health status. This study provides insights into self-reported health status among older people in the context of rural setting of Nepal. The result of this study can inform to develop programs aimed at promoting good health status and reducing disparities in health status among older people.